Evaluasi Program Literasi Digital Disabilitas Fisik di Yayasan Fajar Sejahtera Indonesia Medan - Vivo Mei Ester Tambunan; Fajar Utama Ritonga (Yayasan Literasi Sains Indonesia, 2024)
Physical disabilities are people who experience disturbances in the function of a person's body movements or limbs, which are caused by various factors including disease, accidents or congenital abnormalities. The limitations of physical disabilities cause many negative views from the non-disabled community in general. Furthermore, digital literacy is the ability not only to read but also to understand, comprehend the meaning, integrate and evaluate information presented on a computer. To create people with physical disabilities who understand digital literacy, the Fajar Sejahtera Indonesia Foundation or YAFSI in Medan took the initiative to create a digital literacy program for people with disabilities, especially physical disabilities, together with its partners, namely the Indonesian Disability Care Community or MPDI. The results of the researcher's research stated that this program provides digital access for physical disabilities, so that physical disabilities will experience prosperity, increase self-confidence and be able to keep up with digital developments. This research was carried out using qualitative research methods and data collection techniques were carried out using library research, namely taking information from books, journals, news and others as well as field studies, namely conducting interviews and documentation during the research.